Thermodynamic Analysis of CRDI-VCR Type Diesel Engine Fueled with Moringa Oleifera Biodiesel - Vasant Patel; Vyomesh Buch (Journal of Heat and Mass Transfer Research)
The purpose of the present study is to examine the impact of Compression Ratio (CR) on energy and exergy efficiency of a Variable Compression Ratio (VCR) and Common Rail Direct Injection (CRDI) type diesel engine powered by a blend of diesel and biodiesel from Moringa oleifera. Experiments are performed at four distinct CRs of 15:1, 16:1, 17:1, and 18:1 at 100% loading condition with a fixed engine speed of 1500 rpm, Injection Timing (IT) of 23°before top dead center (bTDC), and Injection Pressure (IP) of 600 bar. Analysis was done on the energy and exergy potential of the fuel input, cooling water, exhaust gas, first and second law efficiency, entropy generation, and Sustainability Index (SI). The energy analysis results show that for all tested fuel blends, an increase in CR results in a decrease in fuel inlet energy, exhaust gas energy, and unaccounted losses, as well as an increase in cooling water energy and energy efficiency. The highest energy efficiency reported for the diesel and biodiesel blend MB30 was 27.20% and 28.13%, respectively, at a higher CR of 18:1. The maximum cooling water energy reported for diesel and biodiesel blend MB30 was 4.09 kW and 4.36 kW, respectively, at a higher CR of 18:1. The reported minimum energy of the exhaust gases for the diesel was 2.74 kW and for biodiesel blends MB10, and MB20 it was reported as 2.95 kW for both blends at a higher CR of 18:1. Across all tested fuel blends, the fuel exergy rate, exergy rate of exhaust gas, and destructed energy decrease as CR increases which results in improvements in entropy generation, SI, and exergy efficiency. The highest exergy efficiency reported for the diesel and biodiesel blend MB30 was 26.31% and 27.21%, respectively, at a higher CR of 18:1. The maximum SI reported for the diesel and biodiesel blend MB30 was 1.36 and 1.37respectively at a higher CR of 18:1. The minimum entropy generation reported for diesel and biodiesel blend MB30 was 0.019kW/K and 0.016 kW/K at higher CR of 18:1.An investigation of the thermodynamics of methyl esters of Moringa oleifera oil mixed with diesel in a VCR-CRDI type engine shows that the combination consists of CR 18:1 and fuel blend MB30 at full load condition offers better performance.